Learning Interest: How Does the Experimentation Compare Between the TAI and TEL Models? - Patriasya, Pitra Gosha; Baharudin, Baharudin; Zulaikhah, Siti; Isti’ana, Ais; Hasanah, Ida Faridatul; Azizah, Nurul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aims to investigate the experimentation of applying the Team Assisted Individualization (TAI) and Technology Enhanced Learning (TEL) learning models on students’ interest in Islamic Education at SMP Negeri 23 Bandar Lampung. The research employs a quantitative approach with a quasi-experimental design. The population of this study includes all eighth-grade students of SMP Negeri 23 Bandar Lampung in the 2024/2025 academic year. The sample used consists of classes VIII D and VIII F, which were designated as the experimental groups, while class VIII E served as the control group, selected using a simple random sampling technique. Data collection was conducted using a questionnaire as a post-test instrument to measure students’ interest in learning. Data analysis techniques included normality tests, homogeneity tests, and one way anova tests. The results of this study indicate that the learning interest of students treated with the Team Assisted Individualization (TAI) and Technology Enhanced Learning (TEL) models was better than that of students treated with conventional learning models. This is based on the results of anova data analysis, which showed an F-value of 18.973 with a significance level of Sig. = 0.000. This value indicates that Sig. < 0.05, leading to the rejection of H?. This means there is a significant difference between the average learning interest in the experimental and control classes. These results suggest that the learning models applied in this study have a significant influence on students’ interest in learning.